Trillion Game. Volume 5 - Inagaki, Riichiro (VIZ Media, 2025)
"In his quest to build a media empire, Haru delves deep into the core of the entertainment business! Meanwhile, Gaku's drive to develop a game seems to be smooth sailing with the addition of Hebijima, the genius game developer, but can they iron out all the bugs?"--Back cover.